Using OER to spark learning and cut costs - Foster, Ali (My University, 2017)
Increasing textbook costs are forcing faculty to make difficult decisions about what resources to include in their courses. What if you could include high quality, low- or no-cost resources instead? Attend this session to learn more about how you can locate and integrate Open Education Resources (OERs). This session will discuss the common misconceptions surrounding OERs, the continuing development of OERs and the Open Education community, and some tools and best practices for incorporating OERs into your teaching to enhance student learning while at the same time lessening the financial strain placed on students enrolled in your courses.
Presented on March 28, 2017 at the Centre for the Advancement of Faculty Excellence (CAFE) at MacEwan University in Edmonton, Alberta.
Keywords: Open Education Resources; open textbooks; instruction; creative commons; higher education